Pulmonary Artery Smooth Muscle Cell Senescence Promotes the Proliferation of PASMCs by Paracrine IL-6 in Hypoxia-Induced Pulmonary Hypertension - Wang, Ai-Ping; Yang, Fang; Tian, Ying; Su, Jian-Hui; Gu, Qing; Chen, Wei; Gong, Shao-Xin; Ma, Xiao-Feng; Qin, Xu-Ping; Jiang, Zhi-Sheng (Frontiers in Physiology, 2021)
Pulmonary hypertension (PH) is a critical and dangerous disease in cardiovascular system. Pulmonary vascular remodeling is an important pathophysiological mechanism for the development of pulmonary arterial hypertension. Pulmonary artery smooth muscle cell (PASMC) proliferation, hypertrophy, and enhancing secretory activity are the main causes of pulmonary vascular remodeling. Previous studies have proven that various active substances and inflammatory factors, such as interleukin 6 (IL-6), IL-8, chemotactic factor for monocyte 1, etc., are involved in pulmonary vascular remodeling in PH. However, the underlying mechanisms of these active substances to promote the PASMC proliferation remain to be elucidated. In our study, we demonstrated that PASMC senescence, as a physiopathologic mechanism, played an essential role in hypoxia-induced PASMC proliferation. In the progression of PH, senescence PASMCs could contribute to PASMC proliferation via increasing the expression of paracrine IL-6 (senescence-associated secretory phenotype). In addition, we found that activated mTOR/S6K1 pathway can promote PASMC senescence and elevate hypoxia-induced PASMC proliferation. Further study revealed that the activation of mTOR/S6K1 pathway was responsible for senescence PASMCs inducing PASMC proliferation via paracrine IL-6. Targeted inhibition of PASMC senescence could effectively suppress PASMC proliferation and relieve pulmonary vascular remodeling in PH, indicating a potential for the exploration of novel anti-PH strategies.